Las estrategias de la angustia en Mientras duermes de Jaume Balagueró: una inmersión en el corazón del mal cotidiano - Bracco, Diane (Romanica Silesiana)
After the excesses of his previous terror movies, the Spanish director Jaume Balagueró returns to a more sober narrative to explore the mechanisms of anguish in an oppressive thriller behind closed doors, Sleep Tight (Mientras duermes, 2011). Influenced by Hitchcock and Polański, he proposes a new variation on the spatial motif of a building which becomes the nest of daily evil embodied by César, an ominous concierge who intrudes into the residents’ intimacy and endeavors to ruin their existence. The present article aims at analyzing the principal filmic and narrative strategies of anguish deployed in this movie. The director elaborates a Manichean costumbrista tale where he probes the atavistic fear of a nocturnal monstrous presence that may perturb the reassuring normality of domestic space. Through the construction of a rigorous rhetoric of repetition, Balagueró places the viewer in a disconcerting narrative in-between and invites him to participate actively in the pernicious game orchestrated by his protagonist, depicted as a methodical agent of everyday terror. Key words: terror cinema, Jaume Balagueró, anguish, space, costumbrismo